A STUDY ON TEACHERS’ STRATEGIES IN MINIMIZING STUDENTS’ SPEAKING ANXIETY AT 11th GRADE SMAN 2 TEMBILAHAN - Taufiq Budiman Yasin; Edi Ardian; Agus Mustajib (J-Shelves of Indragiri (JSI), 2020)
The problem of this research was students’ speaking anxiety seems high. Therefore, the purpose of this research is to know “what teachers’ strategy in minimizing students’ speaking anxiety at the second grade of SMAN 2 Tembilahan are”. This research was descriptive quantitative research. The researcher was distributing questionnaires and interviewing two English teachers as samples to know their strategies in reducing students' speaking anxiety. The sample was taken by using total sampling because there are only two English teachers there. After collecting the data, the researcher found that teachers use many teaching activities to help students' anxiety problems. They used many teaching activities, such as small group work, pair work, simulations, and structure exercises. Besides, the teachers also motivate students to be positive thinking in learning English.